Objects of Vision : Making Sense of What We See - Saab, A. Joan (Book collections on Project MUSE., 2020)
"Advances in technology allow us to see the invisible: fetal heartbeats, seismic activity, cell mutations, virtual space. Yet in an age when experience is so intensely mediated by visual records, the realization that knowledge gained through sight is inherently fallible takes on troubling new dimensions. This book considers the ways in which seeing, over time, has become the foundation for what we think we know. Through a series of linked case studies that highlight moments of seeming disconnect between seeing and believing--hoaxes, miracles, spirit paintings, manipulated photographs, and holograms, to name a few--A. Joan Saab interrogates the relationship between "visions" and visuality. Accessibly written and thoroughly enlightening, Objects of Vision is a concise history of the connections between seeing and knowing that will appeal to students and teachers of visual studies and sensory, social, and cultural history."--back cover.